Ginsenoside Rk1 reprograms ‘cold’ cancer cell membranes into a ‘hot’ antigen repertoire for highly immunogenic cancer vaccines - Fangming Dong; Linlin Qu; Lebin Wang; Jing Zhao; Zhiguang Duan; Xueqing Yu; Xiaoxuan Ma; Daidi Fan (Chemical Engineering Journal, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

Fungal necromass dominates soil organic carbon accrual after decadal active restoration of alpine grassland - Shijie Zhou; Jinchao Gong; Keqi Fan; Abraham Allan Degen; Jingjing Wu; Xiongkui Lin; Tahmina Kausar; Yue Xiu; Linlin Li; Liang Tie; Ziwei Yang; Congyu Ma; et al. (Journal of Environmental Management, 2026)

Modified grafted starch flocculant for the treatment of coal chemical gasification gray water: Synergistic turbidity and hardness removal - Lixin Li; Sinan Liu; Fan Yang; Mingyu Han; Zilong Dong; Caiyu Sun; Linlin Huang; Zhichao Feng; Miyi Luo; Lizhi Tian (Journal of Water Process Engineering, 2026)

Lactobacillus paracasei PC18 fermentation enhances the functional and hypoglycemic properties of soluble dietary fiber from lotus root residue. - Hongzhi Zhang; Lingyu Li; Anthony Pius Bassey; Zhiwei Fu; Yongsheng Zhu; Kaiyan Liu; Linlin Fan; Xiaoli Liu (Food Research International, 2026)

A coordinated control framework for maneuvering and power management in autonomous all-electric ships - Tiewei Song; Lijun Fu; Linlin Zhong; Yaxiang Fan; Meng Zhang (Ocean Engineering, 2026)

Lactiplantibacillus plantarum enables metal recovery from spent LiNi0.33Co0.33Mn0.33O2 cathode via EPS-mediated synergistic bioleaching - Min Li; Hong Wang; Danni Zhang; Zhong Li; Qiuli Xia; Xianjun Guan; Yaojie Yu; Linlin Tong; Junting Tong; Yongqiang Fan; Fuhui Wang; Dake Xu (Journal of Hazardous Materials, 2026)

Multi-measure ecological restoration drives phytoplankton succession and shifts community assembly in an urban eutrophic lake - Xiaowen Lin; Xiaodong Wu; Xuguang Ge; Fan Xun; Weixiang Ren; Mengdie Zhou; Chenxin Zhong; Chunyan Xiao; Linlin Lei (Ecological Engineering, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Advances in the understanding of spatiotemporal distribution and hazard assessment of volcanic tsunamis - Kan Zhang; Linlin Li; Peng Du; Tingting Fan; Weitao Wang; Peizhen Zhang (Science China Earth Sciences, 2026)

Mediating Effect of Self-Efficacy Between Self-Perceived Burden and End-of-Life Communication Difficulties in Cancer Patients - Yalin Zhu; Linlin Shi; Yuanyuan Jiang; Yuyan Fan; Huixian Zhang; Shouxia Chai; Yan Li (Journal of Cancer Education, 2026)

A high-order Model-free Dynamic Framework for Accurate Daily Streamflow Prediction - Jiaying Zhang; Shiqian Tang; Longxia Qian; Mei Hong; Yong Zhao; Linlin Fan (Water Resources Management, 2026)

Zonal asymmetry of recent heat content change in Antarctic Intermediate Water - Xubin Ni; Ling Du; Linlin Fan; Huangyuan Shi (Journal of Oceanology and Limnology, 2026)

Intelligent Recognition Network for Difficult Airway Based on Multi-View Input and Attention Aggregation - Fan Zhang; Jiaqiang Zhang; Zhaoxiang Zhang; Ke Yang; Linlin Zhao; Yuelei Xu (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Thermal performance assessment of coupled soil stratification and groundwater advection effects on vertical borehole heat exchanger - Linlin Zhang; Dongyang Fan; Yanbin Li; Tianhao Yuan; Jun Chen (Geothermics, 2026)

Inactivation of Penicillium ochrochloron spores by pulsed light: Mechanism and preservation efficacy in strawberries - Xiaozhen Cui; Anthony Pius Bassey; Fan Wang; Shudong Xie; Dongnan Li; Linlin Fan; Yongsheng Zhu; Li Bin; Xiaoli Liu (Food Control, 2026)

Engineering yeast expression platforms: Advanced strategies for heterologous protein production and glycosylation modification - Hao Li; Taichi Chen; Zikun Zhang; Qiyi Jiang; Weigang Yuwen; Linlin Qu; Rongzhan Fu; Chenhui Zhu; Huan Lei; Daidi Fan (Chemical Engineering Journal, 2025)

Ginsenoside, a potential natural product against liver diseases: a comprehensive review from molecular mechanisms to application - Shiyan Shang; Haixia Yang; Linlin Qu; Daidi Fan; Jianjun Deng (Critical Reviews in Food Science and Nutrition, 2025)

Cornus officinalis polysaccharides nano-selenium exhibits anti-fatigue effects by regulating gut microbiota in mice - Jianrui Sun; Ruirui Ren; Jinglan Li; Jiaqi Fan; Linlin Yao; Shanshan Tie; Jie Zhang; Dahong Wang; Shaobin Gu (Food Bioscience, 2025)

Dynamic reversible thermochromic camouflage smart textiles for temperature visualized personal healthcare and thermal management - Weiyi Zhang; Shuo Luan; Yuyan Fang; Linlin Zhu; Yang Yang; Mingwei Tian; Lijun Qu; Tingting Fan; Jinlei Miao (Chemical Engineering Journal, 2025)

Simultaneous accelerating H2O2 generation and activation via construction of CuS/NiS2 heterostructures in heterogeneous electro-Fenton for sulfamerazine degradation - Chenlin Wang; Chunhui Yu; Yuhan Ma; Fan Yang; Xinyang Sun; Kexin Wei; Junpu An; Li Li; Linlin Han; Kuobo Wang; Yongfeng Li (Journal of Environmental Chemical Engineering, 2025)

Enhanced selective oxidation of 5-Hydroxymethylfurfural with a recyclable V34@Fe3O4/C catalyst Enriched with Mixed-valence polyoxovanadate active centers - Chunhui Zhang; Mengqi Wang; Changhao Zhao; Junpeng Wang; Yundong Cao; Linlin Fan; Hong Liu; Guang-Gang Gao (Fuel, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

Sponge-like PNIPAM/Fe3O4/PPy composite hydrogel actuator with rapid response, self-sensing and multiple manipulating manners for complex application scenarios - Xingchen Cui; Bing Zhang; Pingzhi Shao; Linlin Li; Shunsheng Ye; Fuqiang Fan; Yu Fu; Fanbao Meng; Tieqiang Wang (Chemical Engineering Journal, 2025)

Bioleaching of valuable metals from spent lithium iron phosphate batteries using food-grade Lactobacillus acidophilus - Qiuli Xia; Danni Zhang; Zhong Li; Chuanwei Yang; Pan Liu; Hong Wang; Yuting Jin; Min Li; Jia Dong; Xianjun Guan; Linlin Tong; Yongqiang Fan; et al. (Chemical Engineering Journal, 2025)

Constructing artificial interphase layer of polyoxovanadates with high oxidizability and reversibility to boost dendrite-free lithium metal anode - Yihai Song; Jiayuan Zhang; Chunhui Zhang; Linlin Fan; Jian Song; Yundong Cao; Yi Feng; Hong Liu; Guanggang Gao (Chemical Engineering Journal, 2025)

Norgestrel shows androgenic properties and triggers reproductive neuroendocrine toxicity in the testes of Pacific oysters (Crassostrea gigas) - Yan Fang; Baojun Liu; Juan Wang; Haoyang Zhong; Linlin Fan; Yuchao Huang; Changkun Chen; Songtao Lu; Tao Zheng (Journal of Hazardous Materials, 2025)

Chronological and Causal Perspectives on the Tectonic Evolution of Equatorial Atlantic - Roufida Rana Djaroun; Linlin Fan; Yanming Huang; Jinchang Zhang (Journal of Ocean University of China, 2025)

Hesperidin-loaded self-assembled supramolecular hydrogel based on quaternized chitosan as efficient photothermal antibacterial dressing for MRSA-infected wound healing - Yamin Xiong; Yi Hao; Linlin Ding; Jinjin Li; Yuan Cao; Shuhui Fan; Fangxia Guan; Leiliang He (Carbohydrate Polymers, 2025)

Distribution of glucosinolates and antioxidants in different leaf-layers of Kale (Brassica oleracea var. acephala DC.) - Yafang Luo; Huixia Bai; Linlin Zhao; Qi Hu; Xinyuan Li; Zhenyu Fan; Yushu Wang (Physiology and Molecular Biology of Plants, 2025)

Fertilization type affects the genetic potential for phosphorus mineralization but not for phosphorus solubilization at the continental scale - Yanhong Yuan; María Belén Barquero; Yu Li; Shuiqing Zhang; Hongzhu Fan; Huimin Zhang; Qiang Li; Shutang Liu; Linlin Shi; Andong Cai; Chengjie Ren; Minggang Xu; et al. (Applied Soil Ecology, 2025)

A coupled model of nonlinear dynamical system and deep learning for multi-step ahead daily runoff prediction for data scarce regions - Longxia Qian; Wei Hu; Yong Zhao; Mei Hong; Linlin Fan (Journal of Hydrology, 2025)

Recovery of high-value metals from the cathode of spent lithium-ion batteries via acid leaching: A review - Kaleab Bizuneh Gebeyehu; Linlin Chen; Linjing Fan; Yanhong Chao; Wenshuai Zhu (Journal of Environmental Chemical Engineering, 2025)

Ginsenoside Rk1 Ameliorates Non-Alcoholic Fatty Liver Disease by Targeting CD36 to Modulate the AMPK Signaling Pathway - Yuqing Wu; Zhiguang Duan; Linlin Qu; Yannan Liu; Xiaoxuan Ma; Daidi Fan (Food Research International, 2025)

The emulsion-filled gels with different fat contents exhibit various friction behavior and dynamic fat-related texture perception at different temperatures - Yueji Zeng; Sihan Zhang; Ke Fan; Shuo Mu; Yang Luo; Linlin Wang; Xiankang Fan; Fuqing Wang; Ran Wang; Jie Luo (Food Quality and Preference, 2025)

Screening of hypoglycemic and probiotic properties of Pediococcus acidilactici FM-Pa-JXM94 and exploring the potential hypoglycemic mechanism - Ying Wang; Hui Zhang; Xingna Wang; Yu Zhang; Linlin Fan; Yanhong Ma; Xiaoli Liu (Food Bioscience, 2025)

Enhanced viability of Lactiplantibacillus plantarun by encapsulation with whey protein isolate fibrils and polysaccharides through layer-by-layer coating - Siyuan Li; Wei Su; Yu Zhang; Wanling Gan; Xiaoli Liu; Linlin Fan (Food Hydrocolloids, 2025)

Tendon injury repair strategy driven by supramolecular hydrogen bonding and dynamic covalent bond self-assembly microspheres - Taishan Liu; Xiaoxuan Ma; Chenhui Zhu; Yu Mi; Jing Zhao; Linlin Qu; Huan Lei; Daidi Fan (Chemical Engineering Journal, 2025)

Huge challenges of improving ozone pollution in China: High regional background ozone concentrations calculated from observational data - Yusi Liu; Yang Zhang; Fan Yang; Linlin Liang; Guiqian Tang (Environmental Pollution, 2025)

Dust removal process of the multi-filter cartridges and its optimization measures for coal dust pollution: Experimental and numerical investigations - Geng Fan; Li Linlin; Huang Ruoxi; Li Shihang; Shi Wentao; Chang Binbin; Peng Zhengbiao; Xia Yuyang (Journal of Environmental Chemical Engineering, 2025)

Utilizing zeolitic imidazolate framework-8 for enhanced carbon dioxide/methane separation and improved carbon dioxide methanation performance - Weiqi Zhang; Xin Kong; Linlin Bo; Delin Yin; Zhichun Zhang; Xiaojun Fan; Hongping Chen; Jin Yuan (Bioresource Technology, 2025)

Environmental heterogeneity drives the spatial distribution of macrobenthos in the Yellow River Delta wetland - Qinglu Fu; Jiao Wang; Debin Sun; Jianyu Chi; Wenzheng Fan; Yu Li; Yilin Wang; Baoquan Li; Linlin Chen (Aquatic Sciences, 2025)

Antifungal activity and active compound identification of Myrothecium spp. against grape anthracnose and gray mold - Linlin Gao; Yijie Zhai; Jiajia Wu; Yuwei Li; Yanchun Fan; Junqiang Guo; Xiping Wang; Zhi Li (Pesticide Biochemistry and Physiology, 2025)

Physicochemical properties and structure of rice dough and protein based on TGase combined with sodium metabisulfite modification - Xuyang Ren; Wanshan Yang; Huining Zhang; Yang Yu; Xiaofeng Hu; Hongchen Fan; Linlin Liu; Mingshou Lv; Ying Sun; Yanguo Shi; Yanling Hao; Fenglian Chen (Food Chemistry, 2025)

Enhancement of farinographic characteristics of rice dough and rice bread quality with combined chemical and enzymatic approaches - Huining Zhang; Wanshan Yang; Yuhan Jiang; Haoyu Li; Menglu Yang; Zhiqi Wang; Bing Wang; Linlin Liu; Hongchen Fan; Fenglian Chen; Ying Liu (Food Bioscience, 2025)

Fabrication and characterization of gelatin/carboxymethyl chitosan composite film incorporated with carvacrol and its preservation efficacy in Chinese mitten crab (Eriocheir sinensis) - Anthony Pius Bassey; Xiaozhen Cui; Isaiah Henry Ibeogu; Fan Wang; Mustapha Muhammad Nasiru; Hadiza Kabir Bako; Linlin Fan; Xiaoli Liu (Food Hydrocolloids, 2025)

In2O3 modification mitigates Jahn-Teller effect in LiMn2O4 enhancing lithium extraction efficiency and stability - Linlin Chen; Linjing Fan; Delin Lan; Jun Gu; Chen Xiaojun; Haiyan Ji; Yanhong Chao; Peiwen Wu; Wenshuai Zhu (Chemical Engineering Journal, 2025)

Ferroptosis-Related Gene Signatures in Epilepsy: Diagnostic and Immune Insights - Xueying Li; Lei Wu; Linlin Sun; Han Liu; Xuezhu Qiao; Na Mi; Shi Yan; Xinyu Zhang; Kun Wang; Pusheng Quan; Fan Yang; Lifen Yao (Molecular Neurobiology, 2025)

Force decomposition of vortex–plate interaction via dynamic mode decomposition - Dehan Yuan; LinLin Kang; Guangmin Dai; Mingming Ge; Dixia Fan (Ocean Engineering, 2025)

Stability and sensory quality of plant-based milk substitutes made from 36 different oat varieties: Relation with oat kernels attributes - Lulu Cui; Jiani Zhao; Linlin Fan; Aijinxiu Ma; Fang Zhong; Sumei Zhou; Dianzhi Hou (Journal of Cereal Science, 2025)

A highly sensitive fluorescent probe based on functionalised ionic liquids for timely detection of trace Hg2+ and CH3Hg+ in food - Siying Che; Yao Fan; Xuemei Hu; Linlin Yin; Haiyan Fu; Yuanbin She (Food Chemistry, 2025)

Variations on the Thrifty Food Plan: Model diets that satisfy cost and nutrition constraints - Yiwen Zhao; Linlin Fan; Norbert L.W. Wilson; Angélica Valdés Valderrama; Parke Wilde (Food Policy, 2025)

2D manganese-doped calcium carbonate nanosheets as activable MRI/US imaging Guided enhanced calcium influx for Boosted regulatory cell death - Mingya Tan; Linlin Huo; Jie Zeng; Shiqi Zhu; Jianfeng Bao; Mengke Fan; Jiangyang Li; Meiling Liu; Jiayi Zhao; Zhenghuan Zhao (Chemical Engineering Journal, 2025)

Algae-inspired chitosan-pullulan-based multifunctional hydrogel for enhanced wound healing - Taishan Liu; Huan Lei; Linlin Qu; Chenhui Zhu; Xiaoxuan Ma; Daidi Fan (Carbohydrate Polymers, 2025)

An Improved Anticipated Learning Machine for Daily Runoff Prediction in Data-Scarce Regions - Wei Hu; Longxia Qian; Mei Hong; Yong Zhao; Linlin Fan (Mathematical Geosciences, 2025)

LncRNA018392 promotes the proliferation of Liaoning cashmere goat skin fibroblasts by upregulating CSF1R through binding to SPI1 - Mei Jin; Weiyu Fan; Suhe Lv; Tianwei Xue; Linlin Cong; Xinyang Liu; Lixin Cui (Molecular Biology Reports, 2024)

Prospective study on the joint effect of persistent organic pollutants and glucose metabolism on chronic kidney disease: Modifying effects of lifestyle interventions - Dandan Wei; Jiayu Shi; Haoran Xu; Yao Guo; Xueyan Wu; Zhiwei Chen; Taimeng Chen; Huilin Lou; Erbao Han; Guozhen Han; Yumeng Yan; Xiaotian Liu; et al. (Science of The Total Environment, 2024)

Migration of depleted uranium from a corroded penetrator in soil vadose zone in Bosnia and Herzegovina - Cui Li; Yanru Liang; Yin Ye; Fan Chen; Markus Astner; David J. Paterson; Yanlong Chen; Linlin Wang; Paul Guagliardo; Matvei Aleshin; Mario Burger; Peter M. Kopittke; et al. (Journal of Hazardous Materials, 2024)

The Environmental Niche of the Light Purse Seine Fleet in the Northwest Pacific Ocean Based on Automatic Identification System Data - Shenglong Yang; Lijun Wan; Linlin Yu; Jiashu Shi; Weifeng Zhou; Shengmao Zhang; Fei Wang; Zuli Wu; Yang Dai; Keji Jiang; Wei Fan (Journal of Marine Science and Engineering, 2024)
Ecosystem-based fisheries management requires high-precision fisheries information to provide relevant data for natural resource management, assessment, and marine spatial planning. This study utilizes Automatic Identification System (AIS) data from light purse seine vessels from the Chinese mainland that were collected from May to November between 2020 and 2022, along with the corresponding environmental data. By applying boosted regression trees (BRTs) and generalized additive models (GAMs), this study establishes nonlinear relationships between fishing intensity and predictor variables and explores the ecological and environmental drivers behind the spatial distribution of light purse seine vessels from the Chinese mainland in the Northwest Pacific. This research identifies the key influencing factors and reveals significant seasonal preferences for different marine environments in various months, with chlorophyll-a being the primary influencing factor. The predicted fishing effort closely resembles observed data, providing valuable information to support fisheries resource management and planning.

Decadal variation and temporal stability of the macrobenthic community in the Bohai Sea, China - Shaoyu Jiang; Jiao Wang; Wenzheng Fan; Linlin Chen; Jing Chen; Baoquan Li (Marine Pollution Bulletin, 2024)

Ultrasensitive monitoring of PCB77 in environmental samples using a visible-driven photoelectrochemical sensing platform coupling with exonuclease I assisted in target recycling - Lining Su; Guizhen Wang; Linlin Zhao; Yuan Deng; Yujing Guo; Yong Xiao; Huanwen Wang; Chuan Dong; Lifang Fan (Science of The Total Environment, 2024)

Effect of silicon on the distribution and speciation of uranium in sunflower (Helianthus annuus) - Linlin Wang; Yanru Liang; Song Liu; Fan Chen; Yin Ye; Yanlong Chen; Jingjing Wang; David J. Paterson; Peter M. Kopittke; Yuheng Wang; Cui Li (Journal of Hazardous Materials, 2024)

Multistage regulation of LiMn2O4 electrode for electrochemical lithium extraction from salt-lake - Jun Gu; Linlin Chen; Linjing Fan; Guiling Luo; Xiaowei Li; Xiaojun Chen; Haiyan Ji; Yanhong Chao; Wenshuai Zhu (Desalination, 2024)

Effect of sodium selenite on the synthesis of glucosinolates and antioxidant capacity in Chinese cabbage (Brassica rapa L.ssp.pekinensis) - Yafang Luo; Shuang Zhao; Huan Wang; Huixia Bai; Qi Hu; Linlin Zhao; Tianyi Ma; Zhenyu Fan; Yushu Wang (Physiology and Molecular Biology of Plants, 2024)

Deep-sea mining of massive sulfides: Balancing impacts on biodiversity and ecosystem, technological challenges and law of the sea - Astrid Holzheid; Hongbo Zhao; Tony Cabus; Lei Fan; Thomas Kuhn; Linlin Sun; Chunhui Tao; Matthias Haeckel; Duong Hoang; Norman Kelly; Terue Kihara; Bing Li; et al. (Marine Policy, 2024)

Investigation on the exopolysaccharide production from blueberry juice fermented with lactic acid bacteria: Optimization, fermentation characteristics and Vis-NIR spectral model - Suqun Yang; Yang Tao; Xiayidan Maimaiti; Wei Su; Xiaoli Liu; Jianzhong Zhou; Linlin Fan (Food Chemistry, 2024)

Thermal interface materials with low modulus and high thermal conductivity by manipulating multi-branched PDMS network: The disentanglement and entanglement effect of dangling chain - Zhian Zhang; Zhibin Wen; Jiashuo Sheng; Chen Zeng; Jianfeng Fan; Linlin Ren; Xiaoliang Zeng; Rong Sun; Peng Chen (Chemical Engineering Journal, 2024)

Integrative proteomic-metabolomics strategy reveals the regulators and mechanism of enhancing cyclic lipopeptides in the high-cell-density fermentation of Bacillus subtilis S1702 - Bo Zhang; Linlin Xu; Hui Yang; Zhengjun Pang; Wenshuo Zhang; Fenghuan Wang; Huilin Liu; Junfeng Fan; Bolin Zhang (Process Safety and Environmental Protection, 2024)

Integrated assessment of trace elements in a marine ranching area based on multi-species and multi-level biomarkers: a case study in China’s national-level marine ranching demonstration area - Mingzhu Li; Zhixu Chen; Ming Li; Jiugang Zhang; Bingqing Xu; Yanyan Yang; Xiangfei Li; Linlin Fan; Baojun Liu; Tao Zheng; Yan Fang; Fan Li (Frontiers in Marine Science, 2024)
The goal of this study was to evaluate the trace element pollution in a marine ranching area in China based on molecular responses (expression of metallothionein and antioxidant enzyme genes), and biochemical biomarkers (metallothionein content, antioxidant enzyme activities, and malonaldehyde level) in four indicator species. We collected samples of two fish ( Lateolabrax maculatus and Sebastes schlegelii ), one crustacean ( Charybdis japonica ), and one gastropod ( Rapana venosa ) from the western Furong Island marine ranching area and from an adjacent area in March 2022 and measured the trace element content in these indicator species as well as in the seawater and sediment. We found that the bioaccumulation characteristics of trace elements and the response patterns of biomarkers were species specific. Moreover, not every biomarker was significantly correlated with environmental trace element content. We then established two biomarker combinations indicative of trace element pollution in seawater and sediment, respectively, based on the correlation between biomarkers and trace element contents. The selected biomarkers were integrated using integrated biomarker response version 2 (IBRv2). IBRv2 values in the studied marine ranching area were lower than those in the adjacent area. Additionally, these values were consistent with the bioaccumulation of trace elements in the indicator species, the integrated trace element pollution index for seawater, and the potential risk index for sediment. These results show that this multi-biomarker and multi-species IBRv2 approach provided a comprehensive diagnosis of trace element pollution in the marine ranching area. Therefore, its application may be beneficial for marine environmental monitoring and management in view of the ecotoxicological impact of pollutants on organisms.

Recent progress in the antidegradation strategies of two-dimensional transition metal carbides (MXenes) - Ying Li; Yudi Li; Linlin Zhao; Siyu Chen; Siren Guo; Xulin Yang; Pan Wang; Kui Li; Fan Lei; Wei Feng; Zihao Mou; Hanjun Wei (Journal of Environmental Chemical Engineering, 2024)

Energetics of eddy-mean flow interactions in the western tropical Pacific Ocean - Yuchao Hui; Linlin Zhang; Xiaomei Yan; Mengmeng Li; Fan Wang; Dunxin Hu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Exploring Seasonal Variations in Fish Communities: A Study of the Yellow River Estuary and Its Adjacent Waters Using eDNA and Trawl Surveys - Xiaoyang Wang; Fan Li; Fei Shao; Hongjun Song; Na Song; Xiaomin Zhang; Linlin Zhao (Fishes, 2024)
The Yellow River Estuary and its adjacent waters serve as crucial spawning, foraging, and nursery areas for marine organisms, possessing abundant biological resources. Monitoring fish communities provides a baseline for implementing the sustainable utilization of marine resources. In this study, data were collected from 15 spring surface and bottom sites and 17 summer surface sites using eDNA and trawl surveys. The results showed that 37, 40, and 35 fish species were detected using eDNA in the spring (surface and bottom) and summer (surface), respectively, with 38 fish species caught during summer trawling. The dominant species mainly belonged to Engraulidae of Clupeiformes in the spring and Gobiidae of Perciformes in the summer, characterized by smaller-sized, short-lived, and pelagic fish species. The summer surface communities exhibited higher diversity than the spring surface and bottom communities. NMDS analysis revealed a degree of seasonal differences in fish communities and that there may be a lack of vertical stratification in the spring communities. The pH and DO were identified as the key environmental factors affecting the fish community. Additionally, the combination of eDNA and trawl surveys was regarded as a superior survey method. Our study provides valuable information for understanding seasonal fish communities in the Yellow River Estuary and its adjacent waters, contributing to fishery resource management and conservation in the region.

Machine learning reveals the selection pressure exerted by nonantibiotic pharmaceuticals at environmentally relevant concentrations on antibiotic resistance genotypes - Shaojing Sun; Yan Sun; Jialu Geng; Linlin Geng; Fan Meng; Qing Wang; Hong Qi (Journal of Environmental Management, 2024)

Ginsenoside Rk1 induces autophagy-dependent apoptosis in hepatocellular carcinoma by AMPK/mTOR signaling pathway - Huanyan Wu; Linlin Qu; Xue Bai; Chenhui Zhu; Yuan Liu; Zhiguang Duan; Hongyan Liu; Rongzhan Fu; Daidi Fan (Food and Chemical Toxicology, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Preparation and characterization of zein-tannic acid nanoparticles/chitosan composite films and application in the preservation of sugar oranges - Shuangjian Li; Xiaoli Liu; Xiaoqian Zhang; Linlin Fan; Fan Wang; Jianzhong Zhou; Hongzhi Zhang (Food Chemistry, 2024)

Geomorphic adjustments of channel bars in the braided reach of the lower Yellow river from 1986 to 2018 - Jie Li; Junqiang Xia; Lingzhong Kong; Qingfeng Ji; Linlin Li; Fan chen (CATENA, 2024)

Spatio-temporal variability of fishing habitat suitability to tuna purse seine fleet in the Western and Central Pacific Ocean - Shenglong Yang; Lijun Wang; Yingjie Fei; Shengmao Zhang; Linlin Yu; Heng Zhang; Fei Wang; Yumei Wu; Zuli Wu; Wei Wang; Jiayu Shi; Keji Jiang; et al. (Regional Studies in Marine Science, 2024)

Structure-defined viologen-polyoxometalate modified separator dominating endurable Li-S batteries by a synergistic adsorption-electrocatalysis mechanism - Yuxi Zhang; Yundong Cao; Linlin Fan; Guilin Shi; Tianyu Zheng; Hong Liu; Jian Song; Guanggang Gao (Chemical Engineering Journal, 2024)

Integrating photovoltaic noise barriers and electric vehicle charging stations for sustainable city transportation - Kai Zhang; Min Chen; Rui Zhu; Fan Zhang; Teng Zhong; Jian Lin; Linlin You; Guonian Lü; Jinyue Yan (Sustainable Cities and Society, 2024)

PM2.5-bound metals and blood metals are associated with pulmonary function and Th17/Treg imbalance: A panel study of asthmatic adults - Nannan Liu; Dan Wang; Jiayu Tian; Xin Wang; Hao Shi; Caihong Wang; Yi Jiang; Min Pang; Xiaozhou Fan; Jing Zhao; Liangpo Liu; Hongyan Wu; et al. (Chemosphere, 2023)

Spatio-temporal distribution of macrobenthos and benthic ecological health status in the Bohai Sea and the northern Yellow Sea, China - Shaoyu Jiang; Wenzheng Fan; Linlin Chen; Jing Chen; Baoquan Li (Marine Pollution Bulletin, 2023)

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

Damping, soft, and thermally conductive composite elastomer via introducing bottlebrush chains - Shipeng Rao; Xiangliang Zeng; Xiaxia Cheng; Jianfeng Fan; Dongyi He; Linlin Ren; Guoping Du; Xiaoliang Zeng (Chemical Engineering Journal, 2023)

Influence Mechanism of New-type Urbanization on Urban Land Use Efficiency in the Yangtze River Delta, China - Qingke Yang; Linlin Ding; Lei Wang; Chao Liu; Yeting Fan; Ying Li; Yazhu Wang (Chinese Geographical Science, 2023)

Real-time monitoring of mercury(II) in water and food samples using a quinoline-based ionic probe - Siying Che; Linlin Yin; Ming Chen; Yao Fan; Anni Xu; Chunsong Zhou; Haiyan Fu; Yuanbin She (Food Chemistry, 2023)

Interactions between zein and anthocyanins at different pH: Structural characterization, binding mechanism and stability - Shuangjian Li; Xiang Wang; Xiaoqian Zhang; Hui Zhang; Siyuan Li; Jianzhong Zhou; Linlin Fan (Food Research International, 2023)

Combined effects of climatic factors on extreme sea level changes in the Northwest Pacific Ocean - Linlin Fan; Ling Du (Ocean Dynamics, 2023)

Ginsenoside Rh4 remodels the periphery microenvironment by targeting the brain-gut axis to alleviate depression-like behaviors - Jingjing Shao; Xiaoxuan Ma; Linlin Qu; Pei Ma; Rong Huang; Daidi Fan (Food Chemistry, 2023)

Development of Zein/tannic acid nanoparticles as antioxidants for oxidation inhibition of blackberry seed oil emulsions - Shuangjian Li; Siyuan Li; Minhui Gong; Hongzhi Zhang; Linlin Fan; Xiaoli Liu; Jianzhong Zhou (Food Chemistry, 2023)

Study on antibacterial mechanism of electron beam radiation on Aspergillus flavus - Linlin Fan; Lili Li; Feifei Shang; Yuhua Xie; Zhenhua Duan; Qianwei Cheng; Yuqiao Zhang (Food Bioscience, 2023)

Multi-scale ocean dynamical processes in the Indo-Pacific Convergence Zone and their climatic and ecological effects - Yan Du; Fan Wang; Tianyu Wang; Weiwei Liu; Linlin Liang; Ying Zhang; Yunfan Chen; Jiaxing Liu; Wei Wu; Kefu Yu; Jing Zhang (Earth-Science Reviews, 2023)

Metagenomic and extracellular polymeric substances analysis reveals the mechanism of exogenous N-hexanoyl-L-homoserine lactone in alleviating the inhibition of perfluorooctanoic acid on anammox process - Linqin Tang; Chengyuan Su; Cuiping Fan; Linlin Cao; Zhu Liang; Yufeng Xu; Zhengpeng Chen; Qing Wang; Menglin Chen (Bioresource Technology, 2023)

The Environmental Niche of the Tuna Purse Seine Fleet in the Western and Central Pacific Ocean Based on Different Fisheries Data - Shenglong Yang; Linlin Yu; Fei Wang; Tianfei Chen; Yingjie Fei; Shengmao Zhang; Wei Fan (Fishes, 2023)
Understanding the spatial pattern of human fishing activity is very important for fisheries resource monitoring and spatial management. The environmental preferences of tropical tuna purse seine fleet in the Western and Central Pacific Ocean (WCPO) were constructed and compared at different spatial scales based on the fishing effort (FE) data from the available automatic identification system (AIS) and commercial fishery data compiled from the Western and Central Pacific Fisheries Commission (WCPFC), using maximum entropy (MaxEnt) methods. The MaxEnt models were fitted with FE and commercial fishery data and remote sensing environmental data. Our results showed that the area under the curve (AUC) value each month based on the commercial fishery data (1°) and FE at 0.25° and 0.5° spatial scales was greater than 0.8. The AUC values each month based on the FE data at a 1° scale ranged from 0.775 to 0.829. The AUC values based on commercial fishing data at the 1° scale were comparable to the model results based on FE data at the 0.5° scale and inferior to the model results based on FE data at the 0.25° scales. Overall, the sea surface temperature (SST), temperature at 100 metres (T100), oxygen concentration at 100 metres (O100) and total primary production (PP) had the greatest influence on the distribution of the purse seine tuna fleet. The oxygen concentration at 200 metres (O200), distance to shore (DSH), dissolved oxygen (Dox), EKE, mixed layer depth (Mld), sea surface salinity (SSS), salinity at 100 metres (S100) and salinity at 200 metres (S200) had moderate influences, and other environmental variables had little influence. The suitable habitat areas varied in response to environmental conditions. The purse seine tuna fleet was mostly present at locations where the SST, T100, O100, O200 and PP were 28–30 °C, 27–29 °C, 150–200 mmol/m3 and 5–10 mg/m−3, respectively. The MaxEnt models enable the integration of AIS data and high-resolution environmental data from satellite remote sensing to describe the spatiotemporal distribution of the tuna purse seine fishery and the influence of environmental variables on the distribution, and can provide forecasts for fishing ground distributions based on future remote sensing environmental data.

Current recycling strategies and high-value utilization of waste cotton - Linlin Lu; Wei Fan; Xue Meng; Lili Xue; Shengbo Ge; Chen Wang; Shin Ying Foong; Cindy S.Y. Tan; Christian Sonne; Mortaza Aghbashlo; Meisam Tabatabaei; Su Shiung Lam (Science of The Total Environment, 2023)

Lanthanum-modified polydopamine loaded Acinetobacter lwoffii DNS32 for phosphate and atrazine removal: Insights into co-adsorption and biodegradation mechanisms - Siyue Han; Yue Tao; Yunhe Cui; Jiaming Xu; Hanxun Ju; Linlin Fan; Lin Zhang; Ying Zhang (Bioresource Technology, 2023)

Whether increased water‐use efficiency of Picea crassifolia promotes radial growth of trees in the eastern Qilian Mountains - Kai Wang; Xiaohua Gou; Linlin Gao; Wenhuo Liu; Haowen Fan; Weiguo Zhang; Haijiang Yang (International Journal of Climatology, 2022)
Global change, characterized by elevated atmospheric CO 2 concentrations and warming, is profoundly affecting terrestrial forests. However, whether the increasing atmospheric CO 2 concentration has a fertilizer effect on tree growth and whether intrinsic water use efficiency (iWUE) promotes tree growth in semi‐arid regions is not entirely clear. In this study, we evaluated the relationships between tree‐ring widths, δ 13 C values and iWUE of Qinghai Spruce ( Picea crassifolia Kom.) in the eastern Qilian Mountains, northwestern China. We found that the iWUE is significantly consistent with the δ 13 C of rings in the high‐frequency signal, and the relationship between iWUE and tree‐ring width is unstable. The first‐order difference correlation analysis with meteorological data showed that both the iWUE and tree‐ring width were drought‐limited. The radial growth was mainly regulated by water availability in current April and July, while annual variation of iWUE was primarily controlled by that in current July. In the early stage of trees growth, there was a positive relationship between iWUE and radial growth due to the CO 2 fertilization. During the 1970s–2000s, the effect of water availability in July on radial growth increases because of the decreased precipitation in July. This has decreased stomatal conductance, intercellular CO 2 concentration, carbon uptake and growth, contributing to the negatively significant correlation between tree‐ring widths and iWUE ( p

Golden 2-like transcription factor contributes to the major QTL against rice black-streaked dwarf virus disease - Xuejuan Li; Feng Lin; Chenyang Li; Linlin Du; Zhiyang Liu; Wenjuan Shi; Jianying Lv; Xiaoyan Cao; Ying Lan; Yongjian Fan; Yijun Zhou; Tong Zhou (Theoretical and Applied Genetics, 2022)

Urban Land Use Efficiency and Contributing Factors in the Yangtze River Delta Under Increasing Environmental Restrictions in China - Qingke Yang; Lei Wang; Xianhong Qin; Yeting Fan; Yazhu Wang; Linlin Ding (Chinese Geographical Science, 2022)

Interannual variations of the North Equatorial Current/Undercurrent from mooring array observations - Ying Huang; Linlin Zhang; Fujun Wang; Fan Wang; Dunxin Hu (Frontiers in Marine Science, 2022)
Interannual variability of the North Equatorial Current (NEC)/Undercurrent (NEUC) in the northwestern Pacific was investigated with the mooring array measurements at 130°E during 2014-2021, in combination with the satellite altimetry. Mooring observations indicate that the velocity of the NEC/NEUC in the upper 900 m exhibits significant variations on the interannual time scale. The westward-flowing NEC strengthens when the underlying eastward-flowing NEUC weakens, and the NEUC branch at 8.5°N is intensified during the mature phase of El Niño and reaches the maximum velocity during the decay phase of El Niño. The phase of the interannual variation of the currents delays with the increasing latitude, with the signal at 15°N lagging that at 8.5°N by about one year. Based on a 1.5 layer reduced gravity model, the interannual variation is suggested to be controlled mainly by the westward propagating baroclinic Rossby wave induced by the wind stress curl forcing in the central Pacific. Different propagating speed of the baroclinic Rossby wave at different latitudes explains the meridional phase lag of the interannual signal. Empirical Orthogonal Function and vertical mode decomposition analysis suggest that the interannual variation of the NEC/NEUC velocity in the northern part is dominated by surface-intensified signals with a vertical structure of the first baroclinic mode, while that in the southern part is dominated by subsurface-intensified signals which is associated with the combination of the first two baroclinic modes. The low-order mode baroclinic response of the ocean to the wind forcing accounts for the interannual fluctuation of the NEC/NEUC velocity observed by the mooring array.

The involvement of oxidative stress, neuronal lesions, neurotransmission impairment, and neuroinflammation in acrylamide-induced neurotoxicity in C57/BL6 mice - Mengyao Zhao; Linlin Deng; Xiaoxuan Lu; Liqiang Fan; Yang Zhu; Liming Zhao (Environmental Science and Pollution Research, 2022)

Correction to: Circular RNA hsa_circ_0000034 accelerates retinoblastoma advancement through the miR-361-3p/ADAM19 axis - Yanhua Jiang; Fan Xiao; Lin Wang; Ting Wang; Linlin Chen (Molecular and Cellular Biochemistry, 2022)

Two Flavors of Intraseasonal Variability and Their Dynamics in the North Equatorial Current/Undercurrent Region - Zhenxiao Wang; Linlin Zhang; Yuchao Hui; Fan Wang; Dunxin Hu (Frontiers in Marine Science, 2022)
Significant surface-intensified and subsurface-intensified intraseasonal variability (ISV) of the North Equatorial Current/Undercurrent with different periods are detected to coexist with mooring ADCP measurements at 13°N, 130°E. The ISV of the currents in the upper 200 m has a relatively shorter period of 45 days, while the period of the subsurface-intensified ISV between 400 and 800 m is around 85 days. By combining with sea surface height measurements from satellite altimeters and outputs from an eddy-resolving ocean general circulation model, the origin and dynamic mechanism of the two flavors of ISV are investigated. Eddy trajectory tracking and energy analysis indicate that both the surface-intensified and subsurface-intensified ISV are related to locally generated meso-scale eddies near the mooring sites. Stability analysis suggests the surface-intensified ISV is related to the baroclinic instability induced by the vertical velocity shear of the North Equatorial Current. While the generation of the subsurface-intensified ISV is more complex and is partly related to the enhanced barotropic instability induced by the intensified horizontal shear of the subsurface zonal background flow.

Constitutive activation of β-catenin in odontoblasts induces aberrant pulp calcification in mouse incisors - Shijian Deng; Linlin Fan; Yunfei Wang; Qi Zhang (Journal of Molecular Histology, 2021)

Long non-coding RNA HCG18 promotes M1 macrophage polarization through regulating the miR-146a/TRAF6 axis, facilitating the progression of diabetic peripheral neuropathy - Wei Ren; Guangxia Xi; Xing Li; Lingxia Zhao; Kun Yang; Xuemei Fan; Linlin Gao; Hongmei Xu; Jianjin Guo (Molecular and Cellular Biochemistry, 2021)

Circular RNA has_circ_0000034 accelerates retinoblastoma advancement through the miR-361-3p/ADAM19 axis - Yanhua Jiang; Fan Xiao; Lin Wang; Ting Wang; Linlin Chen (Molecular and Cellular Biochemistry, 2021)

Adaptive feeding in the American oyster Crassostrea virginica : Complex impacts of pulsatile flow during pseudofecal ejection events - Linlin Wang; Junting Song; Hongsheng Bi; Matthew Gray; Chunlei Fan; Ming Liu; Xian‐Zhong Mao (Limnology and Oceanography, 2020)
Adaptive feeding is a strategy used by many organisms to maintain growth and reproduction success while encountering varying feeding conditions. Oysters are sessile benthic and non‐siphon filter feeders. Oysters are well adapted to modify the ambient microenvironment through their pumping behavior and particle selection activity. Rejection of unsuitable food particulates bound in pseudofeces via ejection events are an integral part of oyster feeding during which oysters produced strong flow opposite to their inhalant feeding flow. The strong opposite pulsatile flow during the ejection event inevitably disrupts the oyster's normal feeding cycle, but how oysters restart their feeding and allocate their energy consumption during an ejection event has not been investigated. The present study used particle image velocimetry (PIV) to examine the impact of ejection events on the feeding of the American oyster, Crassostrea virginica . The strong pulsatile flow resulting from pseudofecal ejection altered the external flow fields by moving water away from the shell. The initial feeding zone after pseudofecal ejection was relatively narrow, possessed a low pulsatile flow, and did not exploit the full flow field. The feeding zone gradually expanded as the pulsatile flow weakened. The strong shear rate at the stable feeding zone then sustained the feeding flow that facilitated oyster feeding. Furthermore, the volumetric fluxes often increased after the ejection event, suggesting increase in feeding efficiency after ejection events. These PIV studies provide new insight on the interactions between feeding oysters and the surrounding physical environment at small yet ecologically relevant scales.

Review on observational studies of western tropical Pacific Ocean circulation and climate - Dunxin Hu; Fan Wang; Janet Sprintall; Lixin Wu; Stephen Riser; Sophie Cravatte; Arnold Gordon; Linlin Zhang; Dake Chen; Hui Zhou; Kentaro Ando; Jianing Wang; et al. (Journal of Oceanology and Limnology, 2020)

Dynamic features of near-inertial oscillations in the Northwestern Pacific derived from mooring observations from 2015 to 2018 - Shijian Hu; Lingling Liu; Cong Guan; Linlin Zhang; Jianing Wang; Qingye Wang; Jie Ma; Fujun Wang; Fan Jia; Junqiao Feng; Xi Lu; Fan Wang; et al. (Journal of Oceanology and Limnology, 2020)

Multi‐century drought variability in the southern Min Mountains - Xiaoya Yan; Yang Deng; Haowen Fan; Jiajia Su; Linlin Gao; Xiaohua Gou (International Journal of Climatology, 2020)
Information on moisture variability is important for climate adaptation and planning, which is urgently needed for the Jiuzhaigou County after it was hit by a magnitude 7.0 earthquake in August 2017, resulting in potential interactions between the earth surface processes and the hydroclimate. To study the regional hydroclimatic history beyond instrumental records, the first tree‐ring hydroclimate reconstruction, based on Pinus tabuliformis , was conducted in the southern Min Mountains, which is situated close to the areas affected by the Jiuzhaigou earthquake. The reconstruction, spanning from 1684 to 2017, explained 59% of the variance for May–August standardized precipitation evapotranspiration index at a 12‐month scale during 1962–2017. The recent drought, which occurred from 1992 to 2017 was the longest in duration, largest in magnitude, and had the second highest intensity. The most severe single year drought occurred in 1824, which was lower than the long‐term mean by 4 σ and affected several regions in and around the Northeast Qinghai‐Tibet Plateau. The drought reconstruction was consistent with other moisture reconstructions, but dissimilar were also exist during some periods. There was a significant correlation between drought reconstruction and sea surface temperature over many oceans. However, the correlations were unstable over time. This study suggests the importance of developing a density tree‐ring network to identify the spatial and temporal drought variability, as well as long‐term record for understanding regional climate dynamics.

A reverse-transcription loop-mediated isothermal amplification (RT-LAMP) assay for detecting the pathogen of maize rough dwarf disease in China - Linlin Du; Wenjuan Shi; Xuejuan Li; Ying Lan; Feng Sun; Yongjian Fan; Tong Zhou; Yijun Zhou (Australasian Plant Pathology, 2019)

Constitutive activation of β-catenin in ameloblasts leads to incisor enamel hypomineralization - Linlin Fan; Shijian Deng; Xin Sui; Mengmeng Liu; Shuhua Cheng; Yunfei Wang; Yuguang Gao; Chun-Hung Chu; Qi Zhang (Journal of Molecular Histology, 2018)

Osteoprotegerin deficiency causes morphological and quantitative damage in epithelial rests of Malassez - Yunfei Wang; Mengmeng Liu; Shijian Deng; Xin Sui; Linlin Fan; Qi Zhang (Journal of Molecular Histology, 2018)

Synaptobrevin-2 facilitates the trafficking and function of atrial SK2 channel - Tao Li; Xuehui Fan; Yiyan Yu; Linlin Chen; Wenjun Huang; Yan Yang; Jimin Cao; Xiaorong Zeng; Xiaoqiu Tan (Science China Life Sciences, 2018)

The role of Ustilaginoidea virens sclerotia in increasing incidence of rice false smut disease in the subtropical zone in China - Mingli Yong; Qide Deng; Linlin Fan; Jiankun Miao; Chaohui Lai; Hongming Chen; Xiujuan Yang; Shu Wang; Furu Chen; Li Jin; Binghui Yang; Yuanjun Bai; et al. (European Journal of Plant Pathology, 2018)

Reduced deep regional cerebral venous oxygen saturation in hemodialysis patients using quantitative susceptibility mapping - Chao Chai; Saifeng Liu; Linlin Fan; Lei Liu; Jinping Li; Chao Zuo; Tianyi Qian; E. Mark Haacke; Wen Shen; Shuang Xia (Metabolic Brain Disease, 2018)

An integrated approach for water scarcity evaluation—a case study of Yunnan, China - Hongrui Wang; Linlin Fan; Yuan Liang; Cheng Wang (Environment, Development and Sustainability, 2018)

Influence of polymeric carrier on the disposition and retention of 20(R)-ginsenoside-rg3-loaded swellable microparticles in the lung - Xiuhua Wang; Xiao Zhang; Linlin Fan; Huan He; Xiaofei Zhang; Yuyang Zhang; Shirui Mao (Drug Delivery and Translational Research, 2018)

miR-155 promotes cutaneous wound healing through enhanced keratinocytes migration by MMP-2 - Longlong Yang; Zhao Zheng; Qin Zhou; Xiaozhi Bai; Lei Fan; Chen Yang; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

Expression of HIV-encoded microRNA-TAR and its inhibitory effect on viral replication in human primary macrophages - Li Li; Haimin Feng; Qin Da; Honglin Jiang; Lang Chen; Linlin Xie; Qiuling Huang; Hairong Xiong; Fan Luo; Lei Kang; Yan Zeng; Haitao Hu; et al. (Archives of Virology, 2016)

NF45 overexpression is associated with poor prognosis and enhanced cell proliferation of pancreatic ductal adenocarcinoma - Chunhua Wan; Chen Gong; Li Ji; Xiaorong Liu; Yayun Wang; Liang Wang; Mengting Shao; Linlin Yang; Shaoqing Fan; Yin Xiao; Xiaotong Wang; Manhua Li; et al. (Molecular and Cellular Biochemistry, 2015)